2021
DOI: 10.3389/fphys.2021.776826
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Clock in Lepidoptera

Abstract: With approximately 160,000 identified species of butterflies and moths, Lepidoptera are among the most species-rich and diverse insect orders. Lepidopteran insects have fundamental ecosystem functions as pollinators and valuable food sources for countless animals. Furthermore, Lepidoptera have a significant impact on the economy and global food security because many species in their larval stage are harmful pests of staple food crops. Moreover, domesticated species such as the silkworm Bombyx mori produce silk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 158 publications
(405 reference statements)
0
39
0
Order By: Relevance
“…Over the years, studies have indicated the oscillating expression of core clock genes in lepidopterans, including various strains of B. mori , and in the monarch butterfly cell line, DpN1 ( Zhu et al, 2008 ; Brady et al, 2021 ). The findings of the present study show that knocking out clock genes of per , tim , Clk , cyc , and cry2 disrupts temperature-dependent diapause induction in silkworms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the years, studies have indicated the oscillating expression of core clock genes in lepidopterans, including various strains of B. mori , and in the monarch butterfly cell line, DpN1 ( Zhu et al, 2008 ; Brady et al, 2021 ). The findings of the present study show that knocking out clock genes of per , tim , Clk , cyc , and cry2 disrupts temperature-dependent diapause induction in silkworms.…”
Section: Discussionmentioning
confidence: 99%
“…CRY2, a clock factor that forms the core feedback loop, is the major transcriptional repressor of CLK/CYC-mediated transcription, whereas PER is associated with CRY2 stabilization rather than with active transcriptional repression ( Reppert, 2007 ; Zhu et al, 2008 ; Zhan et al, 2011 ). These findings suggest that extensive functional diversity exists among species with regard to cry genes and that clock genes participating in the core feedback loop have been evolutionally selected in insects ( Reppert, 2007 ; Tomioka and Matsumoto, 2015 ; Beer and Helfrich-Forster, 2020 ; Brady et al, 2021 ).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is difficult to say what the effect the deletion may have. The lepidopteran circadian clock is relatively well described at the level of whole protein interactions (Brady et al, 2021; Zhu et al, 2008), and experimental data exist on the function of specific parts of a few circadian proteins (Zhang et al, 2017), but to our knowledge the lepidopteran TIM protein has not yet been studied at this level of mechanistic detail. Results from silk moths show that, at least on an amino acid sequence level, both TIM and PER contain many of the functional domains described in Drosophila (Iwai et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, the CWO protein acts synergistically with the main period/timeless loop by binding to and repressing several circadian oscillator genes (including tim, per and cwo itself) in the late night, thus forming an essential subloop that helps keep circadian rhytmicity at high amplitude (Kadener et al, 2007;Tomioka & Matsumoto, 2015). While this function has also been inferred in lepidopterans, it has not yet been experimentally confirmed (Brady et al, 2021). Less is known about the function of timeless2 (also known as "mammalian timeless" or timeout), although it appears to help entrain the insect circadian clock to light (Benna et al, 2010), and has been tied to population variation in circadian activity rhythms in rice borer moths (Zhu et al, 2019).…”
Section: Circadian Gene Variationmentioning
confidence: 99%